Cervical transcutaneous vagal neuromodulation in chronic pancreatitis patients with chronic pain: A randomised sham controlled clinical trial. - Janusiya Anajan Muthulingam; Søren Schou Olesen; Tine Maria Hansen; Christina Brock; Asbjørn Mohr Drewes; Jens Brøndum Frøkjær (PLoS ONE)
Background & aims Chronic abdominal pain is the primary symptom of chronic pancreatitis, but unfortunately it is difficult to treat. Vagal nerve stimulation studies have provided evidence of anti-nociceptive effect in several chronic pain conditions. We investigated the pain-relieving effects of transcutaneous vagal nerve stimulation in comparison to sham treatment in chronic pancreatitis patients. Methods We conducted a randomised double-blinded, sham-controlled, crossover trial in patients with chronic pancreatitis. Patients were randomly assigned to receive a two-week period of cervical transcutaneous vagal nerve stimulation using the gammaCore device followed by a two-week sham stimulation, or vice versa. We measured clinical and experimental endpoints before and after each treatment. The primary clinical endpoint was pain relief, documented in a pain diary using a visual analogue scale. Secondary clinical endpoints included Patients' Global Impression of Change score, quality of life and Brief Pain Inventory questionnaire. Secondary experimental endpoints included cardiac vagal tone and heart rate. Results No differences in pain scores were seen in response to two weeks transcutaneous vagal nerve stimulation as compared to sham treatment (difference in average pain score (visual analogue scale): 0.17, 95%CI (-0.86;1.20), P = 0.7). Similarly, no differences were seen for secondary clinical endpoints, except from an increase in the appetite loss score (13.9, 95%CI (0.5:27.3), P = 0.04). However, improvements in maximum pain scores were seen for transcutaneous vagal nerve stimulation and sham treatments as compared to their respective baselines: vagal nerve stimulation (-1.3±1.7, 95%CI (-2.21:-0.42), P = 0.007), sham (-1.3±1.9, 95%CI (-2.28:-0.25), P = 0.018). Finally, heart rate was decreased after two weeks transcutaneous vagal nerve stimulation in comparison to sham treatment (-3.7 beats/min, 95%CI (-6.7:-0.6), P = 0.02). Conclusion In this sham-controlled crossover study, we found no evidence that two weeks transcutaneous vagal nerve stimulation induces pain relief in patients with chronic pancreatitis. Trial registration number The study is registered at NCT03357029; www.clinicaltrials.gov.